2018
DOI: 10.1088/1361-6579/aadfc5
|View full text |Cite
|
Sign up to set email alerts
|

Wave intensity analysis in the internal carotid artery of hypertensive subjects using phase-contrast MR angiography and preliminary assessment of the effect of vessel morphology on wave dynamics

Abstract: This study shows it is feasible to study wave dynamics in the ICA non-invasively. Whilst changes in aortic wave speed confirmed an expected increase in arterial stiffness, this was not observed in the ICA. This might suggest a protective mechanism in the cerebral circulation, in conjunction with the effect of vessel tortuosity. Furthermore, it was observed that ICA shape correlated with wave energy but not wave speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Furthermore, cPWV calculations were performed based on corrected ROIs, which excluded segments with partial axial vessel coverage (see Supporting Figure S1 for an example of partial vessel coverage in an elderly subject). ROI selection with the aforementioned constraint is important especially in older subjects, which are known to have more tortuous cerebral arteries 20 (representative CCA-ICA segment geometries in a young and an elderly subject are shown in Supporting Figure S1). We found that, as long as both CCA and ICA segments are included in the ROI, excluding a relatively large region around the carotid bifurcation did not significantly change the calculated cPWV values ( Figure 6), suggesting that using multiple waveforms throughout the CCA-ICA segment makes the implemented cPWV calculation technique robust to ROI alterations.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cPWV calculations were performed based on corrected ROIs, which excluded segments with partial axial vessel coverage (see Supporting Figure S1 for an example of partial vessel coverage in an elderly subject). ROI selection with the aforementioned constraint is important especially in older subjects, which are known to have more tortuous cerebral arteries 20 (representative CCA-ICA segment geometries in a young and an elderly subject are shown in Supporting Figure S1). We found that, as long as both CCA and ICA segments are included in the ROI, excluding a relatively large region around the carotid bifurcation did not significantly change the calculated cPWV values ( Figure 6), suggesting that using multiple waveforms throughout the CCA-ICA segment makes the implemented cPWV calculation technique robust to ROI alterations.…”
Section: F I G U R Ementioning
confidence: 99%
“…Although TCD is widely available and its recent developments has made it less prone to artefacts of earlier implementations, 15 TCD measurements are operator‐dependent and their application is contingent upon the availability of an acoustic window, which is known to be limited in older subjects 16 . Moreover, TCD‐based PWV quantifications rely on body surface distance to estimate vessel length, which could have limited accuracy, 17‐19 especially in older subjects which are known to have more tortuous internal carotid arteries (ICA) compared to younger adults 20 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the CRADL project has introduced the continuous assessment of regional lung function using Electrical Impedance Tomography (EIT) technology as supportive care for the most common causes of paediatric respiratory failure ( http://cradlproject.org/ ). As part of the project, a textile electrode patient interface for the neonatal EIT measurement (SenTec AG, CH) has been developed and tested to validate its clinical performance in a multicentre clinical study 2 . Results showed the absence of any discomfort for the patients whilst providing a low contact impedance, which ensures that good quality measurements can be taken.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic distensibility, as well as ventriculo-arterial coupling, can be assessed by an established mathematical technique called wave intensity analysis (WIA) ( 11 ). This is traditionally derived from pressure and velocity data, but it can also be formulated using velocity and area, thus rendering the analysis applicable to phase contrast cardiac magnetic resonance (PC-CMR) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%